Utilization of Videonystagmography (Vng) in Diagnosing and Managing Benign Paroxysmal Positional Vertigo (Bppv) - Dukare, Prashant Manohar (Journal of Biomedical and Pharmaceutical Research, 2020)
Background: Videonystagmography (VNG) is a valuable tool in the diagnosis and management of vestibular disorders, particularly benign paroxysmal positional vertigo (BPPV), a common cause of vertigo. Aim: To evaluate the role of VNG in the diagnosis and treatment of BPPV Methods: This study involved 80 patients diagnosed with BPPV, who underwent VNG testing. Inclusion criteria consisted of adults presenting with recurrent vertigo and a clinical diagnosis of BPPV; exclusion criteria included patients with central vestibular disorders or those who had undergone prior vestibular surgery. Results: VNG effectively identified canal involvement in 90% of patients, with a significant correlation between VNG findings and successful treatment outcomes. Conclusion: VNG is a crucial component in the accurate diagnosis and effective management of BPPV, improving patient outcomes through targeted therapy. Keywords: Videonystagmography, BPPV, Diagnosis, Treatment, Vertigo.